Pengalaman Pembelajaran Virtual dari Sudut Pandang Siswa: Sebuah Studi Kasus di Program Studi Pendidikan Bahasa Inggris - Somara, Rakaisa; Nurhidayat, Eka; Nurhidayah, Yayah (English Education and Literature Journal (E-Jou), 2021)
Virtual learning implementation obtained more exposure along with the pandemic situation in Indonesia. The drastic shift taken by the government policy made all formal institutions moved into the full-online course after trusted ordinary, face-to-face classroom routine for years. The purposes of this study are to reveal students' experience and possible challenges in implementing virtual learning at English Education Study Program. The method used in this research was qualitative design with a case study approach. The instruments of this research were questionnaire and interview. The results showed that students enjoyed more flexibility in learning and spent less time and energy to reach campus. They found the course quite challenging to cope with, but students experienced virtual learning as the necessary option in a pandemic situation. The most prominent challenges in this system are infrastructure-related (gadget, internet  connection) and learning arousement.